Can a Theater Acting Intervention Enhance Inhibitory Control in Older Adults? A Brain-Behavior Investigation - Rajesh, Aishwarya; Noice, Tony; Noice, Helga; Jahn, Andrew; Daugherty, Ana M.; Heller, Wendy; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2021)
Purpose: Studies of reactive and proactive modes of inhibitory control tend to show age-related declines and are accompanied by abnormalities in the prefrontal cortex. We explored which mode of inhibitory control would be more amenable to change and accrue greater benefits following engagement in a 4-week theater acting intervention in older adults. These gains were evaluated by performance on the AX-CPT task. We hypothesized that an increase in proactive control would relate to an increase in AY errors and a decrease in BX errors. In contrast, an increase in reactive control would be associated with a decrease in AY errors, no change in AY reaction time, and an increase in BX response time. Further, we posited that an increase in behavioral proactive control would accompany greater cue versus probe activity for previously identified regions in the prefrontal cortex. In contrast, an increase in behavioral reactive control would be accompanied by greater probe activation in these identified brain areas. Materials and Methods: The participants were 179 community-dwelling adults aged 60–89 years who were on average, college-educated. Participants were pseudo-randomly assigned to either an active-experiencing acting intervention condition (n = 93) or the active control condition (n = 86); participant assignment was subject to time of enrollment. Participants in both groups were trained by theater-actor researchers with expertise in acting interventions. In contrast to the active control participants who attended a course on theater acting, the acting-intervention group was required to consistently deploy proactive and reactive control mechanisms. Both groups met two times/week for 75-minutes for four weeks. Participant brain-behavioral performance on the AX-CPT task was evaluated prior to and after this four-week period. Results: No intervention effects were found in favor of proactive control. Behavioral evidence in favor of reactive control was weak. Brain-related benefits to reactive control were illustrated by greater probe-activation in Brodmann areas 6 and 8, relative to controls and pre-intervention. Conclusion: We found some evidence for improvements in reactive control via brain measures, attributed to engagement in the acting intervention.